An examination of the profile and journey of patients with mental illness in the emergency department. (March 2019) - Coates, Dominiek; David, Michael; Roberts, Ben; Duerden, David
Highlights: Mental health presentations consisted of 3.44% of all presentations to the ED. Prevalent presenting issues were anxiety and stress, overdose, and suicidality. Females and those with personality disorder were more likely to present again. The mean LOS in ED was 3.43 h, with 10% of patients in ED for over 8 h. LOS was associated with gender, age, diagnoses and requirement for admission. Abstract: Objective: To examine the profile and journey of patients with mental illness in the emergency departments (ED) of a Local Health District in Australia. There is limited evidence around the patient profile and journey of people in who present to EDs with mental illness, and the aim of this study was to inform the development of a psychiatric emergency service model. Methods: The study design was a retrospective descriptive analysis of routinely collected data of two hospital EDs. Retrospective health care data of patients who presented to the EDs between July 2016 and June 2017 was analysed using descriptive and inferential statistics. Results: Mental health presentations (N = 4506) consisted of 3.44% of all presentations to the Emergency Department, mostly for anxiety and stress, comorbid alcohol and drug issues, and suicidality. Females were more likely to present, and significantly more likely to present multiple times (specifically for age groups 12–17 and over 65). Presenting issues were associated with age and gender for most diagnostic groups, but not with number of presentations, except for personality disorder. 24.83% were admitted to a mental health inpatient unit, 54.34% were referred to a mental health community team, 4.63% medically, and the remaining referred to alcohol and drug services, GPs, or NGOs. Length of stay was associated with gender (female), age (>65) and diagnosis (drug related and eating disorder). Conclusion: There is limited evidence around the patient profile and journey of people who present to EDs for mental health reasons, and this study contributes to this literature.